For an Open Reason and an Illuminated Faith. Benedict XVI between the University of Ratisbona and the University of La Sapienza - Cordovilla, Ángel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The theology of Joseph Ratzinger and the teaching of Benedict XVI have focused on a new and proper articulation of faith and reason. His speeches in the University of Ratisbona (2006) and La Sapienza (2008) render testimony of it. The actual world needs an open reason and an illuminated faith. This relationship is justified with a theological argument (God is logos), an anthropological argument (the human being is capable of finding the truth), and a historical one (Christianism as radical enlightenment). To make this encounter possible, Benedict XVI considers that the University must be really «Universitas», that is to say, a place open to dialog with the cultures from the amplitude of reason, in whose midst can be found a real space for theology in its proper and specific sense. The only authority that can be admitted by the University is the faithful and committed search for the truth.
Keywords: God and Logos; Man and Truth; Christianism and Enlightment; Faith and Reason